Complexity, Resilience, and Human Resource Management: Illustration from Nordic Higher Education - Kekäle, Jouni; Pinheiro, Rómulo (Nordic Journal of Working Life Studies, 2024)
We explore increasing complexity, resilience (how a system adapts and responds to increasing complexity and radical change), and potential human resource management (HRM) responses to change in higher education at a Nordic institution. HRM is seen as a shared function. As an empirical illustration, we interviewed nine leading academics in dominant and leading administrative positions in one Nordic university. Responses to a major change (CoARA) were discussed. We analyze the possible HRM responses in the context of major but fuzzy changes: How do leading academics forming the HRM policy perceive expectations of role change and how do the respon- dents demonstrate resilience when interpreting the early signs of a major change? The overall initial reactions to the change (CoARA) were hesitant. We propose the concept of emergent resilience and a model to describe its dynamics. Potential implications for HRM in the face of complexity and change are discussed.